(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
The word autopsy is derived from the Greek term autopsia, meaning to “see for oneself ” and is the keystone of forensic medicine. The medico-legal autopsies in India are performed at the request of an investigative officer as guided under the Bharatiya Nagarik Suraksha Sanhita (BNSS) 2023, replacing the former Criminal Procedure Code (CrPC) 1973. A com plete and meticulous autopsy is always necessary, as minor omissions can lead to misinterpretation of findings, affecting judicial outcomes. Post-mortem artefacts and handling-related alterations can further complicate the interpretations, resulting in obscure or negative autopsies where no definitive cause of death is established. Incongruities among forensic experts can sometimes create professional disagreements, yet such wide-ranging outlooks can ultimately enhance justice delivery. This article presents a case series highlighting the significance of preserving trivial evidence, conducting a com plete post-mortem examination, and looking at the post-mortem case through an open-eyed approach. Through three post-mortem cases, we demonstrate how scientific rigour, DNA analysis, histopathology, radiology, and toxicology con tributed to solving complicated cases. Our findings highlight the need for a systematic and neutral approach in forensic pathology to prevent wrongful accusations and ensure reliable post-mortem examinations